Beyond Calvinism and Arminianism : an inductive, mediate theology of salvation - Olson, C. Gordon (Carl Gordon) (Lynchburg, VA : Global Gospel Publishers, 2002)
This book presents a unique view of salvation, one which falls in the middle of Calvinism and Arminianism. It deals with the errors found in Calvinism and Arminianism, and resolves polarized views. It provides a theology of assurance and eternal security in Christ, and a simple solution to Hebrews 6. It approaches Scripture with an inductive, bottom-up approach, not deductive. There is given an exegesis of 1000 quoted Scripture passages. The theology of salvation given in this book is gracious and non-legalistic, and is evangelism and missions friendly. --from back of book
What Is a Mediate Theology of Salvation? Part I: The Foundations of Salvation Established. What Is Meant by God's Sovereignty? -- Whatever Happened to God's Image in Humanity? -- How Did World Redemption Dawn before Christ? -- Is Christ's Passion More than an Atonement? -- Part II: The Terms of Salvation Clarified. Why Must Proclamation Be on God's Terms? -- What Must I Do to Be Saved? -- How Can the Dead Believe? --
Previous ed. published under title: Getting the gospel right : a balanced view of salvation truth.
Includes bibliographical references (p. 462-467) and indexes.
Keywords: Salvation -- Christianity; Theology, Doctrinal; Predestination; Free will and determinism -- Religious aspects -- Christianity; Providence and government of God -- Christianity; God -- Omniscience; Calvinism; Arminianism